2021
DOI: 10.4018/jgim.289221
|View full text |Cite
|
Sign up to set email alerts
|

Frugal Knowledge Sharing for Frugal Innovation Diffusion in Africa

Abstract: This study explores mechanisms of frugal knowledge sharing for frugal innovation diffusion drawing upon concepts from social capital and diffusion of innovation theories. Three frugal innovations projects from Uganda, Malawi, and Ethiopia are used to undertake a preliminary appraisal of a proposed theoretical model. The study identifies a frugal knowledge sharing mechanism based on “The Church lady model”. From a practice perspective, the study informs how to leverage social capital to facilitate frugal knowle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…Pentecostal churches can find KM beneficial in preserving institutional memory. Churches including Pentecostal churches often rely heavily on the knowledge and expertise of their members, and may face significant challenges when key members leave or executives retire (Mengesha, Watson, & Negash, 2021). A knowledge management system can help to capture and store critical knowledge, ensuring that it is not lost when key members move on.…”
Section: The Pentecostal Church and Relevance Of Km In Churchesmentioning
confidence: 99%
“…Pentecostal churches can find KM beneficial in preserving institutional memory. Churches including Pentecostal churches often rely heavily on the knowledge and expertise of their members, and may face significant challenges when key members leave or executives retire (Mengesha, Watson, & Negash, 2021). A knowledge management system can help to capture and store critical knowledge, ensuring that it is not lost when key members move on.…”
Section: The Pentecostal Church and Relevance Of Km In Churchesmentioning
confidence: 99%
“…A mastery climate promotes a mindset of continuous learning and skill development (Černe et al, 2017;Feng and Wang, 2019). This emphasis on growth fosters an environment where firms are more likely to take on stakeholder demands as opportunities for innovating (Caniëls et al, 2019;Mengesha et al, 2021;S.K. Singh et al, 2022).…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…This is a fundamental basis for fostering the creation and sharing of frugal knowledge in organization. In turn, valuable frugal knowledge can facilitate the diffusion and sustainability of frugal innovation in terms of frugal functionality, frugal cost and frugal ecosystem (Mengesha et al, 2021). In particular, a few recent studies also revealed the positive impact of TL on frugal innovation potential.…”
Section: Inclusive Leadership and Frugal Innovationmentioning
confidence: 99%
“…Accordingly, firms can achieve better performance, innovation capability and competitive advantage than their competitors if they successfully manage the knowledge capital (Grant, 1996; Le and Lei, 2019). While the concept of social capital refers to “aggregate of actual or potential resources accessible through a durable network of mutual relationships” (Mengesha et al , 2021, p. 5). Social capital inheres in the relations among individuals and is worth resources for social action.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%